Women's Financial Management Behavior in Supporting Education for Sustainable Development (ESD): The Mediating Role of Financial Self-Efficacy - Anak Agung Istri Anom Bintang Pramawati; Tjokorda Istri Agung Putri Gitaloka; I Komang Aditya Mahadiharja; Erwin Andriano Sianturi; Indah Jayanti; Wandri Wandri; Putu Arya Jaka Cakra Sukerta (IAIN Madura, 2026)
This study applies a quantitative approach to analyze the mediating role of financial self-efficacy in the relationship between financial literacy, self-control, and money attitude on women’s financial management behavior in Denpasar City, in the context of supporting Education for Sustainable Development (ESD). From a population of 333,682 women, 100 respondents were selected using the Slovin formula, and the data were analyzed using SEM-PLS. The results reveal that financial literacy and money attitude have a positive and significant effect on financial self-efficacy, while self-control does not show a significant influence. Furthermore, financial literacy, self-control, and financial self-efficacy significantly contribute to financial management behavior, whereas money attitude has no direct significant effect. Financial self-efficacy is found to mediate the effects of financial literacy and money attitude, but not self-control. These findings emphasize the importance of improving financial knowledge and strengthening individual confidence to support responsible and sustainable financial behavior.